Til o’qitish metodikasining dolzarb masalalari - Ibrohimova Durdonaxon (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article discusses the problems that students face in language learning today, as well as the elimination of problems related to the skills of reading, speaking, listening and writing in foreign language learning. gives information about finding a solution against.